Pharmaceutical Efficacy of Gypenoside LXXV on Non-Alcoholic Steatohepatitis (NASH) - Lee, Jin Ha (Biomolecules, 2020)
Ginsenosides have offered a wide array of beneficial roles in the pharmacological regulation of hepatic metabolic syndromes, including non-alcoholic steatohepatitis (NASH), non-alcoholic fatty liver disease (NAFLD), and obesity. Of the numerous ginsenosides, Rg3 has been widely investigated, but there have been few studies of gypenosides (Gyp). Particularly, no study on Gyp LXXV has been reported to date. Here, to firstly explore the pharmacological effects of Gyp LXXV against NASH and the related mechanism, methionine- and choline-deficient (MCD) diet-induced NASH mice and hepatic cells (stellate cells, hepatic macrophages, and hepatocytes) were selected. Gyp LXXV exhibited markedly alleviated MCD diet-induced hepatic injury, inflammation, and fibrosis by down-regulating hepatic fibrosis markers such as α-smooth muscle actin(α-SMA), collagen1, transforming growth factors-β (TGF-β1), tumor necrosis factor-α (TNF-α), MCP-1, interleukin (IL)-1β, nuclear factor κB (NFκB), and GRP78. Remarkably, histopathological studies confirmed that 15 mg/kg of Gyp LXXV administration to MCD diet-induced mice led to effective prevention of liver injury, lipid accumulation, and activation of hepatic macrophages, indicating that Gyp LXXV might be a potential anti-NASH drug.